THE ROLE OF COMMISSIONERS IN THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN BUMN (A JURIDICAL ANALYSIS BASED ON THE LIMITED LIABILITY COMPANY LAW AND THE BUMN LAW) - Ariyanto Soewondo Geni; Budi Santoso; Sihabudin Sihabudin; Hero Samudra (IBLAM Law Review, 2025)
This research examines the involvement of BUMN commissioners in implementing Good Corporate Governance (GCG) based on the Limited Liability Company Law and the BUMN Law. The goal is to analyze how commissioners ensure transparency and accountability, the impact of GCG on BUMN performance, and the challenges they face in supervision. This normative legal research uses statutory, conceptual, comparative, and case approaches. Data were collected through literature and documentation studies, then qualitatively analyzed descriptively with triangulation of data sources, peer review, critical analysis of sources, and consideration of the social-economic-political context in interpretation. Commissioners play a crucial role in ensuring transparency and accountability of BUMN through GCG. GCG implementation enhances the performance of BUMN as both a development agent and a business entity. However, there are obstacles such as independence, competence, nomination, and limited commissioner authority. The findings emphasize the necessity of strengthening the legal framework and oversight mechanisms to optimize the role of commissioners. The implications include enhancing regulations, supervisory practices, BUMN performance, and strengthening the independence, competence, and authority of commissioners in GCG implementation. This research is important for strengthening BUMN governance. Commissioners have demonstrated their significant role in ensuring GCG and BUMN performance. Further research is required on GCG best practices, its impact on performance, and the factors influencing its successful implementation in BUMN.